Anteseden dari Niat Pembelian pada Generasi Z di Indonesia - Zahwa Dhia Aulia; Brenda Widjaja; Yustian Frendy; Fatik Rahayu (JURNAL AKUNTANSI DAN MANAJEMEN, 2026)
This study aims to analyze the impact of social media influencer endorsements on TikTok on the purchase intentions of Generation Z in Indonesia, with brand awareness and perceived value serving as organism variables. The research is grounded in the Stimulus-Organism-Response (SOR) theory, wherein influencer endorsements act as the stimulus, brand awareness and perceived value function as the organism, and purchase intention represents the response. Primary data were collected through questionnaires from 267 respondents—Generation Z individuals who actively use TikTok and have been exposed to endorsement content—using a purposive sampling technique. The data were analyzed using Structural Equation Modeling (SEM) with the AMOS program. The results indicate that social media influencer endorsements do not have a direct effect on purchase intention. The findings suggest that such endorsements are insufficient to drive purchase intention directly without mediating or moderating variables, such as brand trust or brand attitude. This study contributes theoretically to the development of Stimulus-Organism-Response (SOR) theory within the context of digital marketing and offers practical implications for marketing managers in designing more effective influencer marketing strategies.